Estudio de factibilidad para la creación de una microempresa dedicada a la producción y comercialización de lápidas decorativas hechas con vidrio reciclado en la ciudad de Quito. - Haro Flores, Juan Carlos (2013)
The development of this project aims to determine the feasibility of installing a micro for the production and marketing of decorative tombstones made from recycled glass in the north of the city of Quito, will be based on data obtained from research and direct sources indirect. With these data we will be forced to develop the project in a sustainable and lasting for good nice of all the resources that involve you in it, giving as a result the creation of microenterprises. Upon completion of the analysis and the above investigation we can get a clear understanding of the situation and current market conditions in the range of marketing and production of decorative tombstones. Allowing us to obtain a judgment about whether it is feasible or not to install it.